1996
DOI: 10.1111/j.1525-1594.1996.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Silicone Rubber Membrane by Plasma Induced Graft Copolymerization as Artificial Cornea

Abstract: In this study a highly biocompatible polymer membrane was prepared by surface modification. An artificial cornea was also developed for clinical applications. Silicone rubber (SR) membrane was grafted with hydrophilic monomers such as 2‐hydroxyethyl methacry‐late (HEMA) and acrylic acid by plasma induced grafted polymerization. Surface properties of the SR were characterized using secondary ions mass spectra, Fourier transform infrared/attenuated total reflection, and element spectra for chemical analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Also, the KPro should be exible and should have sufficient tensile strength to allow surgical manipulation and xation. So far, developing a KPro has been attempted by many groups, [12][13][14][15][16][17] among which, the most promising articial cornea is the PHEMA KPro explored by Chirila group. [18][19][20][21][22][23][24] The PHEMA KPro had been assessed by replacing the damaged regions of the cornea of different animals, and found that the KPro could be retained longer than 3 years in some animals.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the KPro should be exible and should have sufficient tensile strength to allow surgical manipulation and xation. So far, developing a KPro has been attempted by many groups, [12][13][14][15][16][17] among which, the most promising articial cornea is the PHEMA KPro explored by Chirila group. [18][19][20][21][22][23][24] The PHEMA KPro had been assessed by replacing the damaged regions of the cornea of different animals, and found that the KPro could be retained longer than 3 years in some animals.…”
Section: Introductionmentioning
confidence: 99%
“…15 But the poor hydrophilicity and biocompatibility of silicone elastomers limit their application scope. Plasma surface modification can improve the surface properties of the silicone elastomers, especially the adhesion and growth of cells on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Neste trabalho foram utilizadas a espectroscopia em infravermelho, a microscopia eletrônica de varredura e o teste de hidrofilicidade. Há vários trabalhos que utilizaram a espectroscopia para análise de copolímeros de enxerto, dentre eles os de Hisue e col. (1992 e 1994) e Lee e col. (1996) [52][53][54] .…”
Section: Caracterização Dos Biomateriaisunclassified
“…estudaram extensivamente a aplicação de hidrogéis poliméricos em diferentes substratos e suas correspondentes propriedades de biocompatibilidade [44] . Hisue e col. [52][53] e Lee e col. [54] estudaram a enxertia do PHEMA em borracha de silicone através da enxertia induzida por plasma para a obtenção de córneas artificiais.…”
Section: Imobilização Da Toxina Marcadaunclassified